Analysis of the effect of sodium valproate sustained release tablets on epilepsy control and cognitive improvement in elderly patients - Xu, Guixing; Xiao, Fang; Liu, Hua; Zheng, Donghua (International Journal of Advances in Medicine, 2020)
Background: To study the effect of sodium valproate sustained release tablets on epilepsy control and cognitive function improvement in elderly patients. Methods: Study was conducted from January 2018 to December 2019, the elderly epilepsy patients admitted in our center were prospectively collected and divided into experimental group and control group according to the method of random number table. The experimental group was treated with sodium valproate sustained-release tablets, and the control group was treated with carbamazepine tablets. The epilepsy control rate and cognitive function improvement of the two groups were observed. Results: total of 71 patients entered the study, including 36 in the experimental group and 35 in the control group; the epilepsy control rate (p = 0.03) and the improvement of cognitive function (p = 0.01) in the experimental group were better than those in the control group. Conclusions: Sodium valproate sustained-release tablets can improve the epilepsy control rate and cognitive function of elderly epilepsy patients, but it needs further large samples and external data validation.